Pokazateli effektivnosti sorevnovatel'noj dejatel'nosti v bokse s ucetom razlicnych formul vedenija boja - Avarkhanov, M. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The article is devoted to the issues of the competitive activity of boxers. The key provisions for the preparation of athletes for participation in high-level competitions are presented. The main characteristics of the training of boxers are investigated, the features of the technique and tactics of combat are revealed depending on the setting of the combat. Methodical recommendations for changing training loads are proposed.